2008
DOI: 10.1677/erc-07-0130
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutation, but not RET/PTC rearrangements, is correlated with a lower expression of both thyroperoxidase and sodium iodide symporter genes in papillary thyroid cancer

Abstract: A low sodium iodide symporter (NIS) expression has been shown in papillary thyroid carcinomas (PTCs) harboring the BRAF V600E mutation. In the present study, we analyzed the mRNA expression of thyroid differentiation genes, glucose transporter (GLUT)-1 and GLUT-3, in 78 PTCs according to the presence of BRAF V600E or RET/PTC rearrangements. We found BRAF V600E and RET/PTC rearrangements in 35.8 and 19.4% of PTCs respectively. The mRNA expression of NIS and thyroperoxidase (TPO) genes were significantly lower (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 38 publications
9
84
0
4
Order By: Relevance
“…Additionally, the BRAF mutation occurs most commonly in aggressive subtypes of PTC [178,201]. Loss of NIS and TPO are early markers of dedifferentiation and they are also responsible for poor prognosis in BRAF positive PTCs [202]. According to these results, the BRAF mutation is a potential independent prognostic molecular marker for PTC.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 96%
“…Additionally, the BRAF mutation occurs most commonly in aggressive subtypes of PTC [178,201]. Loss of NIS and TPO are early markers of dedifferentiation and they are also responsible for poor prognosis in BRAF positive PTCs [202]. According to these results, the BRAF mutation is a potential independent prognostic molecular marker for PTC.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 96%
“…Although the BRAF mutation and RET/PTC rearrangements were generally found to be associated with carcinomas in these studies, the PAX8-PPARγ rearrangement was also detected in follicular adenoma cases. A summary of literature analysis relating to genetic studies in thyroid lesions is shown in Table 3 (2,10 (53,54). The coexistence of the BRAF V600E mutation and RET/PTC rearrangement was not detected in any subject in our study.…”
Section: Discussionmentioning
confidence: 62%
“…The point mutation of BRAF is the most common genetic alternation and is present in approximately 45% of cases of PTC. Some of the other genetic alternations, such as the point mutation of RET/PTC3 rearrangement and the V600E mutation of the BRAF gene, suggest an aggressive phenotype and poor outcome in PTC patients (5,12,15). The BRAF mutation was even considered a predictor of recurrence in PTC patients with extra-thyroid invasion and lymph node metastasis (12).…”
Section: (95% Ci) P-value -------------------------------------------mentioning
confidence: 99%